The Design Of Network Monitoring System Using SNMP Protocol With Telegram Notification - Vingestin, Iga; Kalsum, Toibah Umi; Mardiana, Yessi (Jurnal Media Computer Science, 2023)
One of the network monitoring systems that use SNMP protocol using Nagios. Nagios is an open source application for monitoring and has many plugins, one of which is through Telegram. Where the monitoring results report can be sent via Telegram in real time. This SNMP protocol has many features such as IP Address-based relationships, can exchange data, configure other devices, monitor networks, monitor other devices. With the many features and capabilities of the SNMP protocol, this protocol can be used for network monitoring. From a series of tests carried out by the network monitoring system using the SNMP protocol with telegram notifications running well, according to the design and configurations implemented. Starting from the installation of linux ubuntu server, LAMP Server (Apache2, PHP and MySQL) and the Nagios Core System, then login to the Nagios core system, after successfully logging in, a dashboard page appears that can be used to display network monitoring results in real time..